2016
DOI: 10.5539/jas.v8n12p33
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Perception and Adaptation Strategies on Climate Change in Lower Eastern Kenya: A Case of Finger Millet (Eleusine coracana (L.) Gaertn) Production

Abstract: Eastern Kenya, a semi-arid region, is characterized by low and erratic rainfall, high temperatures, and low soil fertility. Climate change has further worsened the situation leading to frequent droughts and hence increased food insecurity. Traditional crops like finger millet are possible solutions to combating changing climate due to their drought resistance nature, ability to produce high yields with little inputs and high nutritional content. It is against this backdrop that a survey was carried out in Mwal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…According to the farmers, they needed to know when the rains will start in order to decide what farm practices to follow in order to trigger early planting and new tillage methods. These were considered good coping mechanisms to respond to erratic weather patterns (Yvonne et al, 2016). To satisfy these needs, Recha et al (2013) found that the farmers visited the local meteorological station in Machakos to obtain agro-meteorological information and agricultural advisories from meteorologists.…”
Section: Weather and Climate Information Needs Of Farmersmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the farmers, they needed to know when the rains will start in order to decide what farm practices to follow in order to trigger early planting and new tillage methods. These were considered good coping mechanisms to respond to erratic weather patterns (Yvonne et al, 2016). To satisfy these needs, Recha et al (2013) found that the farmers visited the local meteorological station in Machakos to obtain agro-meteorological information and agricultural advisories from meteorologists.…”
Section: Weather and Climate Information Needs Of Farmersmentioning
confidence: 99%
“…A highly variable rainfall pattern and resultant impacts are some of the main factors influencing the use of seasonal forecasts in Machakos (Ouma, 2015). It is for these reasons that many farmers have been using WCI in Machakos since rainfall patterns have changed in the last several years following occurrences of frequent droughts, pests, and diseases (Recha et al, 2016;Yvonne et al, 2016;Gichangi and Gatheru, 2018). In recent years, direct engagements with weather forecasters by farmers in Machakos have been important in motivating them to use forecasts in their decision-making.…”
Section: Key Factors That Influence the Uptake Use And Adoption Of Weather And Climate Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Green gram is considered as a legume suitable for cultivation in the ASALs due to its ability to perform well under the dry conditions found in the semi-arid regions [6]. Since green gram performs well in dry conditions, with this dryness expected to worsen with future climate change, green gram may be a better crop for subsistence farmers to survive the expected effects of climate change.…”
Section: Introductionmentioning
confidence: 99%